Controlling the money supply from macroeconomics perspective: Saving interest and exchange rate - Francisca Sestri Goestjahjanti (Universitas Sebelas Maret, 2024)
The M2 money supply over the last five years has tended to increase by 10-12%, which is allegedly due to macro factors, namely, low savings interest and increasing exchange rate requirements, causing rising inflation rates. This research aims to determine the influence of savings interest and the exchange rate on the money supply in Indonesia for the 2004-2023 period. The analysis technique used in this research is linear regression with annual time series data of 20 observation units. This simultaneous model has never been studied by previous researchers. The results of this research analysis provide information that every change in savings interest negatively affects the M2 Money supply by 78.60% and a significant, positive effect between the Exchange Rate and Money in circulation by 78.40%. Meanwhile, simultaneous changes in savings interest and exchange rates have a significant effect on changes in money supply in Indonesia and the influence is substantial at 91.20%. Therefore, the conclusion of this research is, that partially and simultaneously the proposed model exhibits a significant influence between savings interest and the exchange rate on the amount of money circulating in Indonesia. Therefore, it is crucial to pay attention to the current macroeconomic conditions concerning these two factors, especially the stability of the exchange rate, to ensure that it does not increase the money supply and inflation which may reduce people’s purchasing power in Indonesia.